OPTIMALISASI KINERJA MANAJEMEN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) DALAM MENYELESAIKAN KONFLIK DAN MEWUJUDKAN KERUKUNANAN UMAT BERAGAMA DI KOTA TANGERANG SELATAN - Slamet Suwanto; Ngadisah; Nurliah Nurdin; Andi Pitono (GoAcademica Research dan Publishing, 2020)
This study aims to reveal the search for the ideal method for optimizing the performance management of the South Tangerang Religious Harmony Forum (FKUB) in an effort to resolve conflicts and create inter-religious harmony in South Tangerang City. This research is qualitative with a descriptive approach. Purposive technique is used in determining the research subject. The results of this study indicate that the Tangsel FKUB has not implemented organizational management so that its role and performance in the society of South Tangerang are not optimal and optimal. Its presence is not widely known and its benefits have not been widely felt by the community. The researchers created the ESILINARY TRAS model as steps to optimize performance management that must be taken.